Effects of including fodder beet or swedes in a grass, silage and concentrate-based diet on performance, rumen metabolism and N excretion of lactating dairy cows - Juan P. Keim; Víctor Leighton; Mónica Gandarillas; Rodrigo Arias; I. Beltrán; David Pacheco (Animal Feed Science and Technology, 2026)

Mechanistic insights into ureolytic MICP by halotolerant Bacillus pumilus Soc1 for circular valorization of reverse osmosis brine - Dayana Arias; Claudia Vilo; Rodrigo Garrido; Camila Salazar-Ardiles; Manuel Saldana; Karem Gallardo (Journal of Water Process Engineering, 2026)

Synthetic Resistance Inducers: an Alternative to Fungicides for Controlling Gaeumannomyces Graminis in Rice - Iván Rodrigo Urrego-Velez; Cristhian Camilo Chávez-Arias; Sandra Gómez-Caro; Hermann Restrepo-Díaz (Journal of Crop Health, 2026)
Two field experiments were conducted to assess the effects of individual and combined resistance inducers (RIs) sprays on disease severity, physiological performance, and yield components to control crown sheath rot caused by Gaeumannomyces graminis in rice. In the first experiment, individual applications of cinnamaldehyde (CA), botanical extract (BE), nano-silicon (SiNPs), and chitosan (Chi) were compared with fungicide treatment and an untreated control. The second experiment focused on the efficacy of RIs combinations. Disease severity, area under the disease progress curve (AUDPC), leaf gas exchange properties, chlorophyll fluorescence parameters, and agronomic variables were measured in both the experiments. The results showed that individual and combined RIs treatments reduced disease severity [~3.3 and ~3.4%, respectively] and AUDPC [~85 and ~95, respectively] compared to the untreated control ((individual: 5.20 and 198); (combined: 5.40 and 178)), with RIs efficiency similar (35%) to that of fungicide treatment. RIs application improved leaf photosynthetic rate, photosystem II efficiency, and relative chlorophyll content under biotic stress conditions. Grain yield and efficiency per unit area (EUA) were also enhanced by the RIs treatments, particularly BE (10812 kg · ha −1 ; 83.99 kg rice paddy · m −2 · d −1 ) and SiNPs + Chi + BE + CA (~9600 kg · ha −1 ; ~73 kg rice paddy · m −2 · d −1 ) in comparison with untreated plants [(E1:8283 kg · ha −1 ; 62.42 kg rice paddy · m −2 · d −1 ) and (E2:7475 kg · ha −1 ; 54.32 kg rice paddy · m −2 · d −1 )]. These findings suggest that the foliar application of synthetic RIs during the vegetative stage can be an effective component of integrated disease management strategies for crown sheath rot in rice, potentially reducing the reliance on fungicides while maintaining crop productivity and promoting sustainable disease control.

Resistance exercise training similarly improves work efficiency and measured submaximal oxygen consumption during the 6-min walk test in healthy postmenopausal women and breast cancer survivors - Macarena Artigas-Arias; Rodrigo Muñoz-Cofre; Nicolás Vidal-Seguel; Andrea Alegría-Molina; Jorge Sapunar; Rui Curi; Gabriel Nasri Marzuca-Nassr (European Journal of Applied Physiology, 2026)

A Marseillevirus isolate from the Brazilian wetlands - Matheus Felipe dos Reis Rodrigues; Nidia Esther Colquehuanca Arias; Talita Bastos Machado; João Victor Rodrigues Pessoa Carvalho; João Pessoa Araújo Júnior; Luiz Henrique Rosa; Luiz Carlos Junior Alcantara; Rodrigo Araújo Lima Rodrigues; Victória Fulgêncio Queiroz; Jônatas Santos Abrahão (Archives of Virology, 2026)
Marseilleviruses are giant viruses that infect amoebas and have been isolated from various environments. Here, we describe a new strain, isolated from a water sample collected from the Paraguay River in the Brazilian Pantanal, which we have named "Marseillevirus pantanense". Transmission and scanning electron microscopy revealed icosahedral particles approximately 190 nm in diameter. Genomic and phylogenetic analyses show that M. pantanense has a 379,900-bp genome with 496 open reading frames, including 12 ORFans and two tRNAs. Furthermore, phylogenetic analysis places M. pantanense within Marseillevirus lineage A, group I. The findings of in this study underscore the importance of isolating new viruses to expand our understanding of the abundance and distribution of giant viruses in Brazilian biomes.

Electro-absorption as a high-efficiency strategy for continuous H₂S removal from gas streams - Andrea N. Arias-Sanchez; Bryan A. Tiban-Anrango; Justo Lobato; Manuel A. Rodrigo (Journal of Environmental Chemical Engineering, 2025)

Abundance, provenance, and characteristics of plastic beverage bottles in human settlements and on beaches of the Latin American Pacific region: a citizen science study - Ostin Garcés-Ordóñez; Mauricio Ergas; Jostein Baeza-Álvarez; Daniela Honorato-Zimmer; Ninoshka López-Xalín; Nelson Vásquez; Miquel Canals; Diamela De Veer; María Elisa Aguilera; Illiana Arias; Solange Bolaños; Daphne Aguilar Fallas; et al. (Journal of Cleaner Production, 2025)

Removal of Volatile Organic Compounds from Gases with Innovative Electrochemically-Assisted Reactive Absorbers - Andrea N. Arias-Sanchez; Justo Lobato; Manuel A. Rodrigo (Environmental Processes, 2025)
Volatile organic compounds emitted by various industries constitute relevant atmospheric pollutants with a risk to human health. An electrochemically assisted absorption process (electro-absorption) is proposed and evaluated for the treatment of gaseous streams polluted with benzene or xylene as representative VOCs. The main objective of this work is focused on the comparison between the performance of a packed column and a jet mixer as absorption configuration in this electrochemical technology. The results show that the degradation pathway with both configurations is mineralization. The intermediates compounds vary depending on the pollutant, benzoquinone and tolualdehyde are mainly produced in the removal of benzene and xylene, respectively. An increase in the current density applied to the system implies higher removal rates of the pollutants but lower energy efficiencies, with 50 mA cm -2 being the optimum. Furthermore, it was observed that the jet mixer improves the treatment of gaseous streams with VOCs with low water solubility and volatility (as p-xylene) while the packed column is more effective in treating gases polluted with VOCs with high water solubility and volatility (as benzene). The obtained data allow to establish the technical feasibility and functionality of electro-absorption technology as treatment process to remove VOCs from gas streams, which is meaningful for future research perspectives on scalability, economic evaluation and life cycle analysis to validate and expand the current findings.

The GC% landscape of the Nucleocytoviricota - Amanda Stéphanie Arantes Witt; João Victor Rodrigues Pessoa Carvalho; Mateus Sá Magalhães Serafim; Nidia Esther Colquehuanca Arias; Rodrigo Araújo Lima Rodrigues; Jônatas Santos Abrahão (Brazilian Journal of Microbiology, 2024)

Draw me an oxidoreductase reacting with quinones - Marianne Broc; Michael V. Cherrier; Alexandre Uzel; Rodrigo Arias-Cartin; Pascal Arnoux; Gaël Brasseur; Farida Seduk; Bruno Guigliarelli; Stéphane Grimaldi; Pierre Legrand; Fabien Pierrel; Guy Schoen; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Assessment of the effects of heat stress on the production of dairy cows by using two comfort thermal indices in Southern Chile - Rodrigo A. Arias; Fernando Soto; Juan Pablo Keim (Journal of Thermal Biology, 2024)

Catalyst-less efficient electrochemical production of hydrogen peroxide - Fatemeh Mahmoudian; Andrea N. Arias; Cristina Saez; Justo Lobato; Farideh Nabizadeh Chianeh; Manuel A. Rodrigo (Chemical Engineering Journal, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Removal of VOCs using electro-Fenton assisted absorption process - Andrea N. Arias; Rocío Girón-Navarro; Ivonne Linares-Hernández; Verónica Martínez-Miranda; Elia Alejandra Teutli-Sequeira; Justo Lobato; Manuel A. Rodrigo (Journal of Environmental Chemical Engineering, 2023)

Treatment of gaseous streams polluted with H2S: Comparison of electrolytic and electro-Fenton assisted absorption processes - Rocío Girón-Navarro; Andrea N. Arias; Ivonne Linares-Hernández; Verónica Martínez-Miranda; Elia Alejandra Teutli-Sequeira; Justo Lobato; Manuel A. Rodrigo (Chemosphere, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Transcriptional Profiles Reveal Deregulation of Lipid Metabolism and Inflammatory Pathways in Neurons Exposed to Palmitic Acid - M. Flores-León; N. Alcaraz; M. Pérez-Domínguez; K. Torres-Arciga; R. Rebollar-Vega; I. A. De la Rosa-Velázquez; C. Arriaga-Canon; L. A. Herrera; Clorinda Arias; Rodrigo González-Barrios (Molecular Neurobiology, 2021)

Environmental Drivers and Distribution Patterns of Carnivoran Assemblages (Mammalia: Carnivora) in the Americas: Past to Present - Andrés Arias-Alzate; José F. González-Maya; Joaquín Arroyo-Cabrales; Rodrigo A. Medellín; Enrique Martínez-Meyer (Journal of Mammalian Evolution, 2020)

Colletotrichum acutatum M11 can suppress the defence response in strawberry plants - Rodrigo H. Tomas-Grau; Pia Di Peto; Nadia R. Chalfoun; Carlos F. Grellet-Bournonville; Gustavo G. Martos; Mario Debes; Marta E. Arias; Juan C. Díaz-Ricci (Planta, 2019)

Habitat requirements and differential abundance of the culpeo (Lycalopex culpaeus) in the high Andes of southern Ecuador - Marta Guntiñas; Jorge Lozano; Rodrigo Cisneros; Carlos Narváez; Daniela Arias (European Journal of Wildlife Research, 2019)

Carrageenans from nuclear phases of subantartic Mazzaella laminarioides (Gigartinales, Rhodophyta) and graft copolymerization of alkali-modified carrageenan with acrylamide - Franco Arias; Andrés Mansilla; Betty Matsuhiro; Jorge Pavez; Rodrigo Torres; Mauricio Yáñez-Sánchez (Journal of Applied Phycology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Molecular species identification for multiple carnivores - Marta De Barba; Jennifer R. Adams; Caren S. Goldberg; Carisa R. Stansbury; Daniela Arias; Rodrigo Cisneros; Lisette P. Waits (Conservation Genetics Resources, 2014)

Predicting spatially explicit coral reef fish abundance, richness and Shannon–Weaver index from habitat characteristics - Jesús Ernesto Arias-González; Gilberto Acosta-González; Néstor Membrillo; Joaquín Rodrigo Garza-Pérez; José Manuel Castro-Pérez (Biodiversity and Conservation, 2012)

Singular Elasto-Static Field Near a Fault Kink - Rodrigo Arias; Raúl Madariaga; Mokhtar Adda-Bedia (Pure and Applied Geophysics, 2011)

Molecular mapping of two loci that confer resistance to Asian rust in soybean - Danielle C. G. Silva; Naoki Yamanaka; Rodrigo L. Brogin; Carlos A. A. Arias; Alexandre L. Nepomuceno; Antônio O. Di Mauro; Selma S. Pereira; Livia M. Nogueira; André L. L. Passianotto; Ricardo V. Abdelnoor (Theoretical and Applied Genetics, 2008)